Design considerations for active noise control systems implementing the multiple input, multiple output lms algorithm - Snyder, S.D.; Hansen, C.H. (Journal of sound and vibration, 1992)
While research in the field of active noise control has increased dramatically in recent years, practical systems remain scarce. This is due to the demands placed on the active control devices by most realistic (mufti-modal) structural/acoustic systems. When considering the design of an active noise control system for these complex acoustic problems, the design of the “physical” system and the “electronic control” system can be considered separately. This paper considers the design of the electronic control system by examining the effect which system variables have upon the stability of the multiple input, multiple output LMS algorithm. The results obtained here provide some insights into the efficient implementation of the algorithm in an active noise control system.